2018
DOI: 10.1007/s40262-018-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Elagolix in Healthy Women and Women with Endometriosis

Abstract: Elagolix pharmacokinetics were not affected by patient demographics and were similar between healthy women and women with endometriosis. Clinical Trial Registration Numbers NCT01403038, NCT01620528, NCT01760954, NCT01931670, NCT02143713.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 12 publications
4
40
0
Order By: Relevance
“…The minor urinary excretion of radioactivity was consistent with the population PK analysis, where renal function was not associated with elagolix PK parameters [8]. The OATP1B1 genotype was a statistically significant covariate on apparent clearance (CL/F), however the small change in CL/F (14%) was not considered clinically relevant when the poor and intermediate transporter genotypes were combined and compared with the extensive transporter genotype [8]. Figure 6 depicts the disposition and elimination mechanisms of elagolix in humans.…”
Section: Eliminationsupporting
confidence: 83%
See 2 more Smart Citations
“…The minor urinary excretion of radioactivity was consistent with the population PK analysis, where renal function was not associated with elagolix PK parameters [8]. The OATP1B1 genotype was a statistically significant covariate on apparent clearance (CL/F), however the small change in CL/F (14%) was not considered clinically relevant when the poor and intermediate transporter genotypes were combined and compared with the extensive transporter genotype [8]. Figure 6 depicts the disposition and elimination mechanisms of elagolix in humans.…”
Section: Eliminationsupporting
confidence: 83%
“…The disposition of elagolix involves OATP1B1, and higher (less than twofold) plasma concentrations of elagolix were observed in groups of patients and healthy subjects who have two reduced function alleles of the gene that encodes OATP1B1 (SLCO1B1 521T > C). The frequency of this SLCO1B1 521 C/C genotype is generally < 5% in most racial/ethnic groups [8]. The lack of clinical relevance of OATP1B1 genotypes on elagolix exposure is discussed in a later section on population PK analysis.…”
Section: Pharmacogeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of intestinal P‐glycoprotein by elagolix modestly increased digoxin concentrations, with C max increased by approximately 70% and AUC increased by approximately 30% . The population pharmacokinetics of elagolix suggested the only covariate affecting elagolix apparent clearance was OATP1B1, although this covariate did not result in a clinically meaningful change in elagolix plasma exposure . Strong inhibitors of OATP1B1 are contraindicated to be coadministered with elagolix …”
mentioning
confidence: 99%
“…7 The population pharmacokinetics of elagolix suggested the only covariate affecting elagolix apparent clearance was OATP1B1, although this covariate did not result in a clinically meaningful change in elagolix plasma exposure. 10 Strong inhibitors of OATP1B1 are contraindicated to be coadministered with elagolix. 1 In 2 large replicate phase 3 trials, both 150-mg once-daily and 200-mg twice-daily doses of elagolix were found to be safe and effective in improving both dysmenorrhea and nonmenstrual associated pelvic pain in women with endometriosis-associated pain.…”
mentioning
confidence: 99%